Application of DNA metabarcoding on faeces to identify European catfish Silurus glanis diet. Issue 5 (27th March 2017) - Guillerault, N.; Bouletreau, S.; Iribar, A.; Valentini, A.; Santoul, F.
Abstract : In this study, the results of conventional stomach‐content analysis are compared with the recent DNA metabarcoding approach on faeces to identify fish species consumed by non‐native European catfish Silurus glanis in the Garonne River (south‐western France), with a special emphasis on anadromous prey. Fourteen prey species were identified in the stomach contents or faeces, including four anadromous fish species. Despite higher intestine than stomach emptiness, more species were identified through faecal analysis (11 of 14) than through stomach‐content analysis (five of 14) suggesting that DNA metabarcoding on faeces is an efficient, non‐intrusive technique to study the diet of predatory fishes.